Single-phase two-stage photovoltaic inverters with generalized virtual impedance design - Xie, Chen (2016)
With the development of society and economics, more and more energy is consumed. So the problem of the energy crisis and environmental pollution become more and more serious. That is why renewable energy plays an important role in the energy system now. Photovoltaic grid connected power generation represents the development trend of solar energy utilization, and it is becoming the most important way of solar energy utilization. For the single-Phase PV grid-connected system, the paper chose a suitable main circuit topological construction of two stage inverter and analyzed the working principle of the two stage circuit. The single-phase two-stage inverters are commonly used in low power grid-connected photovoltaic systems to transform the PV panels’ DC voltage into AC which is synchronized with the power grid. This passage studied the main topology of the inverter system. The main topology was set by the software—PLECS, from which the result of the simulation was got. In addition, this passage analyzed the component and control which were chosen in the circuit. FFT was also used in the analysis. What’s more, this passage resented a method that could reduce the value of the capacitance. By changing the parameter of the control system, from the result it was seen that the wave form of the current and voltage still could be improved.